(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
This paper deals with the description and illustration of three species of Stylophyllidae from the Calcare di Zu (Zu Limestone) of Late Triassic age. Stylophyllum paradoxum Frech, Stylophyllum polyacanthum Reuss and Stylophyllum pygmaeum Frech are found for the first time in the Bergamo area, associated to the large coral fauna, already described, commonly occurring in the same formation of the Southern Alps.